Portal hypertension due to pre-hepatic blockage - Grinfeld, David; Salvioli, Jorge (Cirugía del Uruguay, 1979)
Portal Hypertension caused by prehepatic block should be suspected in the case of high digestive hemorrhage coupled with important splenomegaly, with maintenance of hepatic function and hypersplenia. Confirmation of diagnosis is obtained by endoscopy which shows gastroesophageal varices and absence of any other type of b!eeding Jesions. Splenoportography confirms diagnosis and locates block topography, besides indicating the type of anastomosis which is convenient or possible. In some cases specially during hemorrhage which cannot be controlled by medica! treatment hemostatic surgery has to be performed. The author's experience comprises 19 cases operated, 13 of them splenorenal anastomosis and 6 hemostatic operations with 11 % fatality rate.